Deciphering agronomic traits, biochemical components, and color in unique green-seeded fenugreek (Trigonella foenum-graecum L.) genotypes - Singh, Ravindra; Meena, Ram Swaroop; Choudhary, Sharda; Meena, Narottam Kumar; Meena, Ram Dayal; Verma, Arvind Kumar; Mahatma, Mahesh Kumar; Yathendranaik, Ravi; Lal, Shiv; Shekhawat, Pooja Kanwar; Bhardwaj, Vinay (Frontiers in Nutrition, 2025)
Fenugreek is a high-value legume known for its potential to enhance human health and combat a variety of diseases and metabolic disorders. This versatile crop has demonstrated promising therapeutic effects in managing obesity, diabetes, cancer, and poor metabolism conditions that have become major global health concerns. Despite the availability of multiple pharmaceutical remedies for these ailments in the market, often times the heavy chemical doses are accompanied by side effects on human body. To investigate the agronomic traits, medicinal potential, and color of fenugreek seeds, this study was conducted and identified fenugreek genotypes with green seed color (GSF1 to GSF10), which can prevent the progression of aforementioned diseases without the hassle of side effects. Ten unique green-seeded fenugreek (GSF) genotypes were compared with five released varieties (yellow-seeded fenugreek; YSF1 to YSF5) as check. The genotypes were assessed during rabi season for 3 consecutive years (2021–22 to 2023–24) in semi-arid Eastern Plain Zone of Rajasthan, India. The findings exhibited that agronomically GSF performed well, almost at par with the YSF. Harvest index (23.21 ± 0.37%) is higher in GSF with very marginal differences in other agronomic traits. The medicinal potential of the GSF showed that GSF6 has nearly 1.5 to 2 times higher insulinotropic 4-hydroxyisoleucine (0.90%) levels compared to the YSF genotypes. This unique non-protein branched amino acid is found in fenugreek seeds. GSF1 has a high concentration of chlorophyll (0.45 mg/100 g), GSF10 has low diosgenin and high 4-OHIle (261.80 mg/100 g and 0.85%, respectively), and GSF9 has low total soluble sugars (TSS; 3.50%). Oil content, phenols, and proteins were found to be higher in GSF making it preferable over YSF. The study further revealed that darkness of green color in the seed is directly related to its chlorophyll content and is directly associated with higher content of 4-OHIle and lower TSS. Among the studied genotypes, harvest index is higher in green-seeded genotypes with maximum seed yield (2473.74 Kg/ha) in genotype GSF8. The superior genotypes GSF1, GSF6, GSF8, GSF9, and GSF10 developed in the study hold potential for future breeding initiatives, aimed at boosting medicinal value, nutritional quality, and productivity.